Effect Of dill (Anethum graveolens) and garden cress (Lepidium sativum) dietary supplementation on growth performance, digestive enzyme activities and immune responses of juvenile common carp (Cyprinus carpio) - Bilen, Soner; Özkan, Oğuz; Alagöz, Kerem; Özdemir, Keriman Yürüten (Elsevier BV, 2018)
Abstract In this study, Bilen et all, studied that the effect of dietary supplementation of dill (Anethum graveolens) and garden cress (Lepidium sativum) on the growth performance, digestive enzyme activities and immune responses of juvenile common carp (Cyprinus carpio) in addition to their disease resistance to Aeromonas hydrophila and Edwardsiella tarda. Common carp were fed for 45 days with two different doses of extracts of plant (1 and 2 g kg−1) in four treatment groups: dill 1 g kg−1 (D1) and 2 g kg−1 (D2) and garden cress 1 g kg−1 (G1) and 2 g kg−1 (G2). At the end of the study, the fish were challenged with A. hydrophila and E. tarda. Results showed that the final fish weight and specific growth rates were higher in the G2 group than in the control group (C) and other experimental groups (D1, D2 and G1) (P   0.05). In the D1 group, FCR was significantly increased. Trypsin activity was significantly decreased in the G2 group. Compared with the control group, amylase activity was the highest in the D2 group (P
Keywords: 2. Zero hunger; 3. Good health